Motives and Communication Style from Begalan Performers at Banyumas Area - Nur Khasidah, Merliana; Turistiati, Ade Tuti; Setyanugraha, R. Satria (Jurnal Komunikasi Profesional, 2024)
The presence of Begalan in wedding traditions is heavily reliant on the communication style of Begalan performers in introducing and preserving Banyumasan culture and language. The purpose of this research was to analyse and comprehend the motivations and communication styles of Begalan performers in the wedding tradition in the Panginyongan area of Banyumas. The qualitative descriptive research method is used in this study. Data collection entails observing, interviewing Begalan performers, and researching relevant literature. According to the findings of this study, 1) the motives of the Begalan performers in carrying out the wedding tradition in the Panginyongan area are ritual, entertainment, and professional motives; and 2) the communication style of the Begalan performers in the wedding tradition in the Panginyongan area of Banyumas tends to use a low context communication style. Another finding in this study is that there are obstacles experienced by Begalan performers, including diverse audiences with different cultures, lack of attention and appreciation from the audience, and lack of availability of the tools used in carrying out the Begalan procession. To overcome these obstacles, Begalan performers innovate using Indonesian and Banyumasan languages, adding to the audience's appeal by making jokes and preparing to get Begalan tools.